The Effect of Capital Quality, Credit Quality, Efficiency and Profitability on Company Value: (Study on Conventional General Banking Companies Listed on the Indonesia Stock Exchange for the Period 2013-2022) - Putria Ananda, Viska; Kusmayadi, Dedi; Rusliana, Nanang (Review on Islamic Accounting, 2024)
The objectives of this research is to determine and analyze capital quality, credit quality, efficiency, profitability and company value in conventional general banking listed on the Indonesian Stock Exchange and the influence of capital quality, credit quality, efficiency and profitability on company value in conventional general banking listed on the Indonesian stock exchange. The research method used in this research is descriptive analysis with a case study approach. The data needed in this research is secondary documentary data which contains the history of company finances published on the Indonesia Stock Exchange (BEI). The data and information obtained from the results of this research were analyzed using panel data multiple regression analysis. Based on the research results, it is known that partially capital quality and profitability have a positive effect on company value, while credit quality and efficiency have a negative effect on company value. Together, capital quality, credit quality, efficiency and profitability have a positive and significant effect on company value in conventional general banking listed on the Indonesian Stock Exchange. It is recommended for conventional general banking companies to improve capital quality and profitability as well as maintain the level of capital quality and efficiency, to increase company value.